Weight Loss Self-Efficacy and Modelled Behaviour: Gaining Competence Through Example - Schulz, Benjamin Rudy; McDonald, Marvin J (Canadian Journal of Counselling and Psychotherapy, 2010)
The Weight Efficacy Life-Style Questionnaire (WEL) and the International Physical Activity Questionnaire (IPAQ) assessed self-efficacy and physical activity for 124 volunteers aged 17–61. It was administered before and after participants attended a video modelling workshop. Half of the participants in the treatment and control groups were given copies of the videos to review at home. Predictions were that self-efficacy would increase most for participants who took home the videos after the group-based intervention that was built on models of successful weight loss behaviours. Self-efficacy was also expected to lead to increased physical activity. Results demonstrated that weight loss self-efficacy can be increased by watching successful models. Physical activity, however, did not increase.